Social Policy Review. 32, Analysis and Debate in Social Policy, 2020 - Rees, James, 1978-; Pomati, Marco; Heins, Elke (Bristol : Policy Press, 2020)
Leading experts in the field present an up-to-date and diverse review of the best in social policy scholarship over the past year. This volume considers current issues and critical debates in the UK and the international social policy field. It contains vital research on race in social policy higher education and analyses how welfare states and policies address the economic and social hardship of young people. The contributors also consider the impacts of austerity on the welfare state, homelessness, libraries and other social policy areas. Published in association with the Social Policy Association, this comprehensive volume will be of interest to students and academics in social policy, social welfare and related disciplines.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Social policy; Race; Racism